The first recombinant FVIII produced in human cells – an update on its clinical development programme. (January 2014) - Valentino, L. A.; Negrier, C.; Kohla, G.; Tiede, A.; Liesner, R.; Hart, D.; Knaub, S.
Summary: The development of inhibitors and the need for frequent venous access for FVIII injection are major challenges in current haemophilia treatment. Presently available recombinant FVIII (rFVIII) products produced in hamster cell lines are associated with inhibitor formation in up to 32% of previously untreated patients. The new human cell line‐derived recombinant human FVIII (Human‐cl rhFVIII) protein is the first native, unmodified truly human rFVIII product produced in a human cell line without additive animal proteins. The aim of using a human cell line for the production of rFVIII is the avoidance of non‐human epitopes on rFVIII, thereby potentially reducing the rate of inhibitor development, avoiding allergic reactions and allowing personalized prophylaxis with the chance of fewer infusions. Studies to date show that prophylaxis with Human‐cl rhFVIII prevents 96% of bleeding events in adults with severe haemophilia A when compared to on‐demand treatment. Available pharmacokinetic data with a mean half‐life of 17.1 h allow personalized prophylaxis with the chance of fewer infusions. Studies in previously treated children and adults indicate that Human‐cl rhFVIII is efficacious and safe in the prevention and treatment of bleeding episodes and that none of the treated patients developed inhibitors or allergic reactions thus far.